Analisis akuntabilitas dan transparansi APBDes Desa Suluan Kecamatan Tombulu Kabupaten Minahasa berdasarkan Peraturan Menteri Dalam Negeri Nomor 20 Tahun 2018 - Mokoagouw, Reyyansi Wicen; Tinangon, Jantje J.; Kapojos, Peter M. (Yayasan Widyantara Nawasena Raharja, 2024)
The Village Budget and Revenue (APBDes) is an annual budget plan of the village government and is the basis for the management of village funds. Village governments are required to manage community funds in a transparent and accountable manner so that the government can record and report on the accounts. The purpose of this study is to determine the accountability and transparency of APBDes of Suluan Village, Tombulu District, Minahasa Regency, based on the Regulation of the Minister of Home Affairs Number 20 of 2018. The method used in this study is qualitative descriptive, which aims to collect data to analyse and describe the systems and procedures of the APBDes. The resource persons in this study are the village head, village secretary, village treasurer and head of government. The results of the study show that the management of APBDes in Suluan Village is based on the Regulation of the Minister of Interior No. 20 of 2018 and the indicators and principles of accountability, transparency and participation. Suluan Village provides good, accountable, transparent, and participatory information such as information through village deliberations and the installation of billboards that make information on village development financing in the APBDes and involve the community, community involvement in the planning process and implementation of the APBDes.